Compliance with goodwill-related mandatory disclosure requirements and the cost of equity capital. Issue 3 (16th April 2017) - Mazzi, Francesco; André, Paul; Dionysiou, Dionysia; Tsalavoutas, Ioannis
Abstract : Theory suggests that increased levels of corporate disclosure lead to a decrease in cost of equity via the reduction of estimation risk. We examine compliance levels with International Financial Reporting Standard 3 Business Combinations and International Accounting Standard 36 Impairments of Assets mandated goodwill-related disclosure and their association with firms' implied cost of equity capital (ICC). Using a sample of European firms for the period 2008–2011, we find a median compliance level of about 83% and significant differences in compliance levels across firms and time. Non-compliance relates mostly to proprietary information and information that reveals managers' judgement and expectations. Overall, we find a statistically significant negative relationship between the ICC and compliance with mandated goodwill-related disclosure. Further, we split the sample between firms meeting (or not) market expectations about the recognition of a goodwill impairment loss in a given year to study whether variation in compliance levels mainly plays a confirmatory or a mediatory role. We find the latter: higher compliance levels matter only for the sub-sample of firms that do not meet market expectations regarding goodwill impairment. Finally, our results hold only in countries where enforcement is strong.